Gestión urbana del recurso pluvial: aproximación histórica (2014)
The article reflects on water management in cities, focusing on two aspects: misspend of potable water in domestic chores such as flushing toilets, and rainwater disinterest that characterized the twentieth century cities, breaking with a tradition of millennia. In the corpus of the article an approach to the history of stormwater management resource in different cultures, continents and eras is pertormed. It is concluded that it is urgent to return to the concept of 'rainwater harvesting' in cities, with contemporary techniques and technologies, for: i) lower the pressure over ecosystems (Iess water abducted); ii) increase urban resilience; iii) reduce flooding in urbanized areas; iv) promote decentralization of wáter resources in cities; v) strengthen water independence of citizens.